Global Forces and Local Responses: The Case of the Mongolia 'Riot', Sydney, 1908. Issue 3 (3rd July 2022) - Simpson, Ian
Abstract : Australian press reports of a 'riot' between two groups of Indian lascars at Circular Quay and subsequent demonstration through Sydney streets in 1908 illustrate the collision between the forces of globalisation – in the form of the transoceanic passage of South Asian seafarers – and those of nation formation and white racial identity, in the response of the local authorities. Australian anxieties over the transgression of space by mobile South Asian labour were confirmed. The incident was a reminder that the ambition of establishing a White Australia behind secure borders had not been achieved successfully.